Periodontal diseases in the Australian adult population. (25th June 2020) - Ha, Diep H; John Spencer, A; Ju, Xiangqun; Do, Loc G
Abstract: Periodontal diseases are some of the major oral diseases and conditions in adults. Objective: The study aimed to present the population patterns of periodontal diseases and trends of periodontitis in the Australian adult population. Methods: Data collected in the recent National Study of Adult Oral Health (NSAOH) 2017–18 were used to present the current population patterns of periodontal diseases. Periodontal assessment was carried out at three sites per tooth for all present teeth, excluding third molars. Prevalence of gingivitis, periodontal pocket depth of 4+ mm, gingival recession of 2+ mm, and clinical attachment loss of 4+ mm were calculated and reported. The US CDC/AAP case definition was used to define cases of moderate to severe periodontitis. NSAOH 2017–18 data were combined with data collected in NSAOH 2004–06 using similar methods to describe age‐ and cohort‐related trends of periodontitis. Results: The prevalence of periodontal diseases and conditions were relatively high in the Australian adult population. Some three in every ten Australian adults had moderate to severe periodontitis. There was a tendency of higher prevalence of periodontitis in NSAOH 2017–18 than in NSAOH 2004–06 among people of the same age. Conclusion: Periodontal diseases and conditions remain a significant problem in the Australian adult population.